What Does the Past Tell Us? A Content Analysis of the First Quarter-Century of the British Journal of Music Therapy. (June 2014) - Tsiris, Giorgos; Spiro, Neta; Pavlicevic, Mércèdes
Professional journals have a legitimating and sanctioning role in the development of disciplinary knowledge, as well as professional practices and identities. The British Journal of Music Therapy (BJMT) – the only UK-based peer-reviewed music therapy journal – has portrayed research, theory and accounts of practices, reflecting trends and developments in the field of music therapy since 1987. Marking the 25th anniversary of the BJMT and looking into its future development, a content analysis of the journal since its inception (1987–2011) was conducted with the aims of (i) tracing trends and developments of music therapy praxes and professional identities, and (ii) exploring the journal's engagement with disciplinary discourses and practices alongside and beyond those of music therapy. The study provides an overview of the BJMT in terms of 1) paper types, 2) authorship: numbers and professional titles, 3) countries of project sites and countries of authors, 4) sample conditions, sizes and ages, 5) formats of practices, and 6) models and themes. The results show that the majority of the articles published in the BJMT are theoretical, focus on one-to-one sessions, are single authored by music therapists and are UK-focused in terms of authorship, project site and models. This study brings to the fore questions for the future development of music therapy as profession and discipline.